Background of diversification of activity of gas transportation enterprises - Ромашко, О. М. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
The article analyzes the factors which affect the reduction in output, deteriorating of financial condition and reducing the competitiveness of gas transportation companies. It was investigated the structure of natural gas consumption by regions, categories of consumers and economic activities and has been revealed a general trend to the reduction of the natural gas consumption in Ukraine. The prediction of gas transit volumes to Europe and critical analysis of the Energy Strategy in part of the functioning the gas-transport system had been made. Based on the analysis, it was determined the specific prerequisites regarding the necessity of the diversification of gas transmission companies.